2011
DOI: 10.1007/s00247-011-2072-9
|View full text |Cite
|
Sign up to set email alerts
|

MRI of acquired posterior urethral diverticulum following surgery for anorectal malformations

Abstract: Pelvic MRI can be a useful tool in the postoperative assessment of suspected PUD associated with ARM. Radiologists should have a high clinical suspicion for a postoperative PUD when a cystic lesion posterior to the bladder/posterior urethra is encountered on two imaging planes in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…31,36 There have been some radiographic reports about posterior urethral diverticulum, and in some cases, posterior urethral diverticula could not be revealed using voiding cystourethrography, being detectable only using MRI. 10,11,16,18 Histopathology of the excised mucosa of the cyst showed colonic mucosa and confirmed that cyst was indeed an enlarged residual rectourethral fistula. 16 To prevent posterior urethral diverticula, novel surgical approaches and enhanced surgical skills are required.…”
Section: Anal Stenosismentioning
confidence: 84%
See 3 more Smart Citations
“…31,36 There have been some radiographic reports about posterior urethral diverticulum, and in some cases, posterior urethral diverticula could not be revealed using voiding cystourethrography, being detectable only using MRI. 10,11,16,18 Histopathology of the excised mucosa of the cyst showed colonic mucosa and confirmed that cyst was indeed an enlarged residual rectourethral fistula. 16 To prevent posterior urethral diverticula, novel surgical approaches and enhanced surgical skills are required.…”
Section: Anal Stenosismentioning
confidence: 84%
“…dysuria, formation of urinary stones, infection, and malignancy. 10,16,18,19 Meanwhile, some patients with posterior urethral diverticula may not exhibit any symptoms. 10,16,18,19 Therefore, it may be accidentally detected on an MRI performed to evaluate the levator ani muscle.…”
Section: Anal Stenosismentioning
confidence: 99%
See 2 more Smart Citations
“…This complication underscores the importance of precisely defining the location of the fistula prior to the index operation-considered by some to be the most important information to be obtained in the preoperative evaluation (26). When evaluating a patient for a redo operation, a PUD/ROOF may be detected via cystoscopy (Figure 4), VCUG or sometimes pelvic MRI (27).…”
Section: Retained Remnant Of the Rectal Fistulamentioning
confidence: 99%